Associations Between Cardiac Troponin, Mechanism of Myocardial Injury, and Long‐Term Mortality After Noncardiac Vascular Surgery. Issue 6 (June 2017) - Reed, Grant W.; Horr, Samuel; Young, Laura; Clevenger, Joshua; Malik, Umair; Ellis, Stephen G.; Lincoff, A. Michael; Nissen, Steven E.; Menon, Venu
Abstract : Background: The time‐sensitive hazard of perioperative cardiac troponin T (cTnT) elevation and whether long‐term mortality differs by mechanism of myocardial injury are poorly understood. Methods and Results: In this observational study of 12 882 patients who underwent noncardiac vascular surgery, patients were assessed for cTnT sampling within 96 hours postoperatively. Mortality out to 5‐years was stratified by cTnT level and mechanism of myocardial injury. During a median follow‐up of 26.9 months, there were 2149 (16.7%) deaths. By multivariable Cox proportional hazards analysis, there was a graded increase in mortality with any detectable cTnT compared to <0.01 ng/mL; cTnT 0.01 to 0.029 ng/mL hazard ratio (HR) 1.54 (95% CI 1.18–2.00, P =0.002), 0.03 to 0.099 ng/mL HR 1.86 (95% CI 1.49–2.31, P <0.001), 0.10 to 0.399 ng/mL HR 1.83 (95% CI 1.46–2.31, P <0.001), ≥0.40 ng/mL HR 2.62 (95% CI 2.06–3.32, P <0.001). Mortality for each mechanism of injury was greater than for patients with normal cTnT; baseline cTnT elevation HR 1.71 (95% CI 1.31–2.24; P <0.001), Type 2 myocardial infarction HR 1.88 (95% CI 1.57–2.24; P <0.001), Type 1 MI HR 2.56 (95% CI 2.56, 1.82–3.60; P <0.001). On Kaplan–Meier analysis, long‐term survival did not differ between mechanisms. The hazard of mortality was greatest within the first 10 months postsurgery. Consistent results were obtained in confirmatory propensity‐score matched analyses. Conclusions: Any detectable cTnT ≥0.01 ng/mL is associated with increased long‐term mortality after vascular surgery. This risk is greatest within the first 10 months postoperatively. While short‐term mortality is greatest with Type 1 myocardial infarction, long‐term mortality appears independent of the mechanism of injury.